Penerapan Model Pembelajaran Project Based Learning pada Matakuliah Struktur Hewan - Setiyadi, Muhammad Wahyu; Putra, Mujiono Sang; Awaluddin, Rizka; Gulbudi, Gulbudi; Zaelani, Muhammad; Firmansyah, Edi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The type of research used in this research is Classroom Action Research. The subjects in this research were students of the Biology Education Study Program, STKIP Al Amin Dompu in the even semester of the 2022/2023 academic year. The instruments used in this research were student activity observation sheets and student cognitive learning outcomes tests. The analysis used in this research is descriptive qualitative. The research results show that the application of the project based learning model can improve students' cognitive learning activities and outcomes. Student learning activity in the pre-cycle was 36.84%, cycle I was 57.88%, and cycle II was 82.45%. Meanwhile, the classical mastery of students' cognitive learning outcomes increased from pre-cycle by 42.1%, cycle I 68.42%, and cycle II by 84.21%.